Prioritizing Innovative Organizational Factors for State-Owned Enterprises (Case Study: Iraq) - Abu Khch, Hussein Basheer; Aghasi, Saeid; Amanah, Ahmed Abdullah; Davoodi, Sayyed Mohammad Reza (Management Strategies and Engineering Sciences, 2025)
The aim of the present study is to prioritize the innovative organizational factors for state-owned enterprises (case study: Iraq). The research is applied in nature and uses a survey method. Data analysis was conducted using the DEMATEL technique. The statistical population consists of managers of state-owned companies in Iraq, as well as academic professors and experts. The sample size includes ten managers from state-owned companies, selected through random sampling. The research instrument is a researcher-developed pairwise comparison questionnaire. The validity of the questionnaire was confirmed through a review by a group of management professors. The results indicate that the criteria for net impact, in order of priority, are: 1) Strategic, 2) Legal, 3) Organizational, and 4) Technical. The criterion for the outcome (net effect) is also identified as the individual aspect. In the examination of the sub-criteria, determining and focusing on innovative strategies was identified as the most influential sub-criterion, while the development of strategic thinking in employees was identified as the most impactful factor.